Achieving a linear magnetostrictive effect in textured MnCoSiGe alloys. (1st January 2023) - Hao, Xiaowen; Yang, Bo; Li, Jie; Wang, Dunhui; Li, Zongbin; Yan, Haile; Zhang, Yudong; Esling, Claude; Zhao, Xiang; Zuo, Liang
Abstract: TiNiSi-Type MnCoSi alloys have attracted much attention as a potential magnetostrictive material, owing to the magnetic-field-induced metamagnetic transition. In the present work, the textured bulk MnCoSi alloys with [100]o preferred orientation were prepared by a multi-stage thermal treatment. Giant magnetostriction was achieved as much as −5268 ppm in the [100]o oriented stoichiometric MnCoSi alloys at 300 K and under a magnetic field of 3 T. The substitution of Si with Ge element results in a linear magnetostrictive behavior in the [100]o oriented MnCoSi0.84 Ge0.16 alloys, which means that large magnetostriction can be obtained under a low magnetic field. The magnetostriction for the MnCoSi0.84 Ge0.16 alloys reaches up to −327 ppm and −330 ppm under a magnetic field of 0.5 T at 280 K and 300 K, respectively. In a magnetic field of 1 T, the magnetostriction of the MnCoSi0.84 Ge0.16 alloys is −923 ppm and −821 ppm at 280 K and 300 K, respectively. Through the systematic investigation of the crystal structure, microstructure, and magnetic properties of the MnCoSiGe alloys, the achievement of a linear magnetostrictive performance is ascribed to the enhancement of magnetization and decreasing of the width of martensite variants. Our work greatly enhances the low-field magnetostrictive performance of MnCoSi-based alloys and makes them of interest in potential applications. Graphical abstract: Image, graphical abstract